Morphometric and molecular identification, domestication, and potentials of stingless bees (Apidae: Meliponini) in Mount Halimun Salak National Park, West Java, Indonesia - MUHAMMAD NABIL PRATAMA; ALI AGUS; NAFIATUL UMAMI; AGUSSALIM AGUSSALIM; HARI PURWANTO (Society for Indonesian Biodiversity, 2023)
Abstract. Pratama MN, Agus A, Umami N, Agussalim, Purwanto H. 2023. Morphometric and molecular identification, domestication, and potentials of stingless bees (Apidae: Meliponini) in Mount Halimun Salak National Park, West Java, Indonesia. Biodiversitas 24: 6107-6118. The purpose of this study is to identify the stingless bee species found in Mount Halimun Salak National Park, Sukabumi, and investigate the potential for its domestication. Four resorts within the Park, Cimantaja, Mount Koneng, Mount Bodas, and Kawah Ratu, were chosen as the sampling sites. The random sampling method was used to collect samples of stingless bees by working with locals. The collected bees were subsequently identified using their morphological and morphometrics features. Two species of stingless bees, Tetragonula laeviceps and Heterotrigona itama were found in the Park. The results of the 16S rRNA mtDNA gene sequencing confirmed the identity of the specimen of the stingless bees. Moreover, 37 colonies of T. laeviceps and 7 of H. itama were collected. The T. laeviceps were found in all four resorts, but the H. itama were only successfully collected from Kawah Ratu resort. The possibility for domestication and meliponiculture was investigated through observation and interviews with locals who shared their knowledge and the meliponiculture practices surrounding the Park. The study showed that T. laeviceps has more potential to be utilized in meliponiculture in the surrounding area of the Park.